CBC6: A new iron biofortified cowpea variety released in Zimbabwe - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Collaboration between HarvestPlus, CGIAR breeding centers, and National Agricultural Research Systems resulted in the release of 21 new varieties of 7 biofortified crops in 8 countries, in 2021. Evidence links point to the biofortification crops map and an internal HarvestPlus database (password required). Breeding reports are available upon request.